Custo social de oportunidade na trajetória de acesso ao ensino superior: o caso dos ingressantes na UFRN nos vestibulares de 2006 a 2010 - Oliveira, Ridalvo Medeiros Alves de (2011)
Access is a problem of higher education in Brazil that has existed since the formalization of this has occurred since the installation of the Portuguese court in Brazil in 1808. Only 10% of young people between 18 and 24 years of age attending this level of education in 2000, arriving in 2010 just 15%, far from that determined the National Education Plan in 2001, triple that percentage by the year 2010. In addition, a majority of seats of public HEIs is populated by students from the private network, especially in high-demand courses. In this context, this study aims to identify the costs related to the trajectories of students who were successful in the vestibular UFRN editions from 2006 to 2010. Presents an overview of higher education in Brazil, a brief history of vestibular, as well as new forms of access, and some of the policies to expand such access, highlighting the argument Inclusion UFRN. Focusing on the theme of the paper presents the concepts of opportunity costs and social. After collecting data through a questionnaire and consultation of databases COMPERVE was developed to search for a descriptive and analytical, with the participation of 3,995 students, of whom 1642 (41.1%) had completed secondary education in schools public, and 2,078 (52%) in private schools. The profile indicates that 90% are single, about 50% are 21 years of age, are white and female. In the course of preparation for college entrance exams, 80% chose the course during or after completion of the last year of high school, and almost 70% said they had started preparing at that time. Findings related to the costs involved with this preparation indicate that, in most cases there were school fees and disbursements and workshops, and the purchase of books and other materials, with parents primarily responsible for this cost, the amount disbursed each month was up $ 300 for 64% of respondents and only 7% of them exceeded $ 1,000, the major non-financial costs were characterized by the following resignations: job opportunities (24%) or temporary work (20%) courses of languages (26%), leisure activities (48%), leisure travel (43%), and parties and / or shows (54%). Of social investments by the government, stand out in the tax waiver scholarships for study in private institutions, grant exemption from the registration fee of vestibular, the preparatory courses UFRN, and seminars by COMPERVE / UFRN with networks of high school. From the junction of the opportunity costs (private costs) and social costs (public costs), a new concept: the social opportunity cost, which measures the combined efforts of families and government to finance the opportunity to access higher education of an individual. This concept can and should be incorporated as a strategic vector for the sake of democratic university, which reflects the social model that is sought